Factors contributing to missed clinic appointments by people living with HIV/AIDS on antiretroviral therapy at a health centre in Capricon District Limpopo Province, South Africa - Marule, Kholofelo Yvonnne (My University, 2022)
Topic : Factors contributing to missed clinic appointments by people living with HIV/AIDS on antiretroviral therapy at a health centre in Capricon District Limpopo Province, South Africa. Background: The approach of the South African healthcare sector concerning the management and reduction of queues at clinics throughout the country was developing a system where patients made appointments. The focus of this study was on patients undergoing antiretroviral therapy and how they have been reported to be missing their appointments. When patients miss their antiretroviral therapy appointments it has a negative impact on operations at the clinic as well as its finances. Aims : The aim was to investigate the contributing factors to missed appointment visits of People Living With HIV for antiretroviral therapy at a Health Centre in Capricorn District, Limpopo. Methodology: A quantitative, cross-sectional descriptive study design was used to achieve the aim of this study and its objectives. Results: one hudred and eighty eight participants took part in the study. Majority were and females. Participants had various reasons for missing appointments, such as the lockdown restrictions (24.4%), the long distance from the healthcare facility (23.9%), and a lack of money for transportation (9.5%). A significant relationship was observed between the year of missed appointments and reasons for missing appointments with p values of 0.01 and 0.03 respectively. The study concludes that most antiretroviral therapy patients miss clinic appointments due to lockdown restrictions.
Thesis (MPH.) -- University of Limpopo, 2022
Keywords: Antiretroviral therapy; Healthcare; People living with HIV; Making appointments; AIDS (Disease) -- Patients; HIV-positive persons; COVID-19 (Disease) -- Complications; Highly active antiretroviral therapy; Hospitals -- Waiting lists